Etiology and Perception of Suicide: Cultural Explanation of Suicide from Javanese Perspective - F A Nurdiyanto; Subandi Subandi (Jurnal Psikologi, 2023)
The suicide rate in Java is increasingly worrying. Furthermore, there is still a limited exploration of suicide in Javanese culture. This qualitative research intended to explore the perception of suicide in the Javanese with Arthur Kleinman’s explanatory model framework. We interviewed 21 Javanese, of which 28.5% had a history of attempted suicide. Grounded theory analysis found that the Javanese have various terms for suicide based on how suicide is conducted, emotional nuances, and influences of taboo. Suicide is believed to be influenced by suffering, loss of hope, alienation, mental frailty, and low religiosity. It is important to consider cultural characteristics in suicide prevention campaigns and suicide management programs. This article encourages cultural sensitivity for clinicians and health authorities to accommodate the Javanese belief in suicide prevention programs as well as the delivery of effective interventions.